Multi-dimensional poverty analysis for Tanzania: First order dominance approach with discrete indicators - Channing Arndt; Vincent Leyaro; Kristi Mahrt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
As in much of sub-Saharan Africa, Tanzania has attained rapid economic growth accompanied by only marginal reductions in poverty. Is this mismatch between high economic growth and less significant poverty reduction due to how growth and poverty are measured and reconciled, or more substantial underlying factors? Applying the first order dominance approach to multi-dimensional welfare comparisons, this paper seeks to gain a greater understanding of the evolution of poverty in Tanzania over time and space. Analysis of welfare indicators among four population groups in the regions, zones, and urban/rural areas of Tanzania reveal broad-based improvements in well-being between 1990 and 2010.
Keywords: F15; F33; L80; 330; multi-dimensional poverty analysis; first order dominance; Tanzania